Global Health and Emergency Care: A Postgraduate Medical Education Consensus‐based Research Agenda. (December 2013) - Martin, Ian B.K.; Jacquet, Gabrielle A.; Levine, Adam C.; Douglass, Kate; Pousson, Amelia; Dunlop, Stephen; Khanna, Kajal; Bentley, Suzanne; Tupesis, Janis P.; Hauswald, Mark
Abstract Global emergency medicine (EM) is a rapidly growing field within EM, as evidenced by the increasing number of trainees and clinicians pursuing additional experiences in global health and emergency care. In particular, many trainees now desire opportunities at the postgraduate level by way of global EM fellowship programs. Despite this growing popularity, little is known of the effects of postgraduate training in global health and emergency care on learners and patients in the United States and abroad. During the 2013 Academic Emergency Medicine consensus conference on global health and emergency care, a group of leading educators at the postgraduate medical education level convened to generate a research agenda of pressing questions to be answered in this area. The consensus‐based research agenda is presented in this article.